Amanu: CNN-RNN Kapampangan Language Learning-Based System for Grade School Learners - John Elmo Gozun Mangune; Marvin Ordoñez Mallari; Arzel Paguio Pinpin (Malikussaleh University, Aceh, Indonesia, 2025)
This study examines the development and implementation of